THE IMPLEMENTATION OF ISO 9001:2015 TO IMPROVE QUALITY OF SERVICE AT PUSAT KESIHATAN UNIVERSITI (PKU), UNIVERSITI UTARA MALAYSIA (UUM) (Journal of Technology and Operations Management, 2018)
The purpose of this study is to review the implementation of ISO 9001:2015 in order to improve the quality of services at Pusat Kesihatan Universiti (PKU), Universiti Utara Malaysia. The respondents of this study were customers at the PKU, UUM. The questionnaire was distributed to 50 respondents. The data were analyzed using SPSS software version 24. The data were tested using descriptive statistics, and correlation analysis to answer the research questions and to achieve the objectives. The findings show that customers agree that implementation of ISO 9001:2015 give service at PKU, UUM is good and satisfied. Through the correlation test, the results showed that the relationship between the implementation of ISO 9001:2015 has a positive and significant impact on customer satisfaction and the effect of implementing ISO 9001:2015 has a positive and significant impact in improving quality of service at PKU, UUM. Through mean and standard deviation tests, results show that tangible dimensions are the main dimensions of customer satisfaction while dimensions with low values are dimensions of responsiveness. Therefore, all aspects of service in PKU, UUM will be strengthened and all aspects of the weaknesses could be addressed to improve the service in order to maintain good quality services.